Strategi Komunikasi Efektif dalam Praktik Keperawatan: Peran Bahasa Tubuh dan Kontak Mata - Rudi Purwana; Mariana Mariana; Asrul Asrul; Afina Muharani Syaftriani; Ani Rahmadhani Kaban (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
Effective communication between nurses and patients is crucial in nursing practice, as it can impact patient outcomes and satisfaction. This study explores the role of body language and eye contact in enhancing communication between nurses and patients. Using a qualitative approach, data were collected through in-depth interviews with 30 nurses from various hospitals in Indonesia. The results indicate that appropriate body language, such as open posture and gentle hand gestures, can increase patient comfort and trust. Additionally, consistent and empathetic eye contact is essential in building stronger and deeper nurse-patient relationships. The findings also show that training and awareness of body language and eye contact can enhance nurses' communication skills. This study recommends that nursing training programs include modules on non-verbal communication to improve the effectiveness of nurse-patient interactions. Consequently, nurses can provide more holistic and patient-centered care, ultimately improving the overall quality of healthcare services.